Perfil de RNA mensageiro de exossomas de soro de indivíduos com adenocarcinoma de pâncreas com diabetes mellitus - Donnarumma, Carlos Del Cistia (2021)
Ductal adenocarcinoma of the pancreas (CP) has a very poor prognosis and is rarely diagnosed early. There is a close association between recent-onset diabetes mellitus (DM) and this neoplasm, with DM being considered a biomarker of CP. On a clinical basis, it is difficult to differentiate DM secondary to CP and type 2 DM (DM2) and the identification of markers that can help in this differential diagnosis would be of great help in clinical practice. The aim of the present study was to compare the messenger RNA (mRNA) profile of exosomes extracted from the serum from three groups of individuals; (1) with CP and recent-onset DM, (2) with long-standing DM2, and (3) without these two clinical conditions (Control group [C]). For this purpose, 20 individuals with CP and recent-onset DM, 22 individuals with long-standing DM2 and 13 control individuals were included. Peripheral blood was collected for isolation of exosomes from 1 mL of serum; exosomes were subjected to total RNA extraction for generation of complementary DNA libraries, which were sequenced. As there was a great variability in the number of genes detected between the samples, those transcripts present in at least 30 samples were considered in the analysis of differentially expressed genes (n=113 genes.) Among these genes, those that presented a statistically significant difference in the comparisons between Groups CP and C, CP and DM and DM and C were selected (n=40 genes). A total of 19 genes were differentially expressed between participants with CP and DM: seven between CP and DM Groups (ASAH1, ULK4, TMSB4X, HBB, HBA2, YWHAB and B2M), nine between CP and C and CP and DM Groups (GIGYF2, MTND1, MTND2, DNMT3A, SHISAL2B, MAP1B, RPS29, MTCO2 and HBA1), two between CP and DM and DM and C Groups (MTND3 and DNASE1) and one between CP and C, CP and DM and DM and C Groups (MTND5). Among the 19 differentially expressed genes, seven had a P value < 0.05 in the ROC curves considering the Groups CP and DM2 (ULK4, GIGYF2, YWHAB, MTND5, MTND1, HBB and DNASE1) and could be used to discriminate recent-onset DM associated with CP from DM2, especially if these findings are validated in an independent population.b